Criteria for Moral Upbringing - Normatova Esonalievna (Penerbit Jurnal Indonesia, 2024)
There are two traditional ways to promote spirituality. The first is through the glorification of human qualities, the definition of people with such qualities, the example. The second way is through the condemnation of vices. This tool is more effective than the first. For this reason, it is necessary to objectively recognize the achievements and assess the shortcomings allowed from a critical point of view. In this article highlights of criteria of moral education.